CAPTURE OF FERGHANA VALLEY BY SHAIBANIKHAN - Lolaxon Teshebaeva (Academia Science Repository, 2023)
The article examines the history of the termination of Ahmad Tanbal's power in Ferghana and the inclusion of the valley into the state of Sheibanikhan.